The Incidence, Associated Factors and in‐Hospital Outcomes of Cardiac‐Surgery‐Associated Acute Kidney Injury Among Children Undergoing Cardiac Surgery at Jakaya Kikwete Cardiac Institute. A Hospital‐Based Prospective Cohort Study - Joyce Gimonge; David Muhunzi; Zawadi Edward; Rodrick Kisenge (Health Science Reports, 2025)
ABSTRACT Background and Aims Cardiac surgery‐associated acute kidney injury (CSA‐AKI) is one of the serious complications that can potentially increase the risk of morbidity, long‐term adverse effects and mortality. Despite the advances in the care and increased survival of children post‐cardiac surgery, CSA‐AKI is still a big problem with considerable morbidity and mortality in high‐risk children. Prevention of CSA‐AKI is important for survival and minimization of long‐term adverse outcomes of children after cardiac surgery. This study aimed to determine the proportion of acute kidney injury, associated risk factors and in‐hospital outcomes among children undergoing cardiac surgery at the Jakaya Kikwete Cardiac Institute (JKCI). Methodology A prospective cohort study was conducted to determine the proportion, risk factors, and in‐hospital outcomes among children who developed cardiac surgery‐associated acute kidney injury (CSA‐AKI) at JKCI. Data collection was done using a structured questionnaire, Intensive care unit (ICU) chart review, and hospital records. Diagnosis of CSA‐AKI was done based on KDIGO criteria. Serum creatinine was measured pre‐operatively and subsequently, daily up to day seven postoperatively to determine the presence of CSA‐AKI. Results A total of 210 children were recruited into the study, of which 120 (57.1%) were males. The median age of the study participants was 36 months. Of the recruited children, 23 (11.0%) developed cardiac surgery‐associated acute kidney injury (CSA‐AKI). Intraoperative hypotension [ARR = 2.7; 95% CI 1.37‐5.26; p‐value = 0.004], intraoperative platelet transfusion [ARR = 2.7; 95% CI 1.37‐5.22; p‐value = 0.004] and two or more days on mechanical ventilation [ARR = 2.3; 95% CI 1.1‐4.71; p‐value = 0.019] were found to be significantly associated with CSA‐AKI. There were 8 (3.8%) deaths, of these, 7 (87.5%) were from children who developed CSA‐AKI. Children who developed CSA‐AKI had, on average, a longer ICU stay, with a mean difference of 1.959 days. Conclusion This study's findings highlighted the prevalence and severity of cardiac surgery associated with acute kidney injury in pediatric patients. The identified risk factors, such as intraoperative hypotension, platelet transfusion, and prolonged mechanical ventilation, provide crucial insights for improving patient outcomes. The study's results also emphasize the need for interventions targeting these modifiable factors to reduce mortality among children undergoing cardiac surgery.